Validity test of "Sigeram" as an android-based biology learning interactive media on human movement system topic - Putri Hapsari; Nurul Hidayati Utami; Noorhidayati Noorhidayati (Assimilation: Indonesian Journal of Biology Education, 2023)
This study aims to describe the suitability of "Sigeram" derived from the acronym "sistem gerak manusia” or human movement system to become an android-based interactive learning media for biology subjects. This study uses descriptive research with four stages, namely analysis, design, development, and validation. The data collection technique used a validity questionnaire. The validity test subjects consisted of three practitioners, including a teacher from Senior Hugh School 12 Banjarmasin and two lecturers from the study program of Biology Education, Universitas Lambung Mangkurat. “Sigeram” application consists of some menus, including learning prerequisites, identity, learning implementation components, meeting schedule, concept map, then the material section, summary, glossary, quiz, bibliography, and profile. Additional features in the interactive media are the "Bio Info", "Let's Find Out", "Let's Discuss", "Act Creatively", "Habituation", "Reflection", and "Final Project". Testing the validity of "Sigeram" as an interactive media for learning Biology based on android showed a validity score of 4.29 with a very valid category, so that "Sigeram" can be used as an interactive media for learning biology, especially in human movement system topic.